Engineering aspects of thermal food processing - Simpson, Ricardo (Contemporary food engineering, 2009)
Addresses fundamental aspects of modelling, simulation, optimization, online control, and computer automation. This book presents advances and ideas in optimizing quality and the required procedures in assuring safety.